The aliphatic amidase AmiE is involved in regulation of Pseudomonas aeruginosa virulence - Clamens, T.; Rosay, T.; Crépin, A.; Grandjean, T.; Kentache, T.; Hardouin, J.; Bortolotti, P.; Neidig, A.; Mooij, M.; Hillion, M.; Vieillard, J.; Cosette, P.; et al. (Nature Publishing Group, 2017)
© The Author(s) 2017.We have previously shown that the eukaryotic C-type natriuretic peptide hormone (CNP) regulates Pseudomonas aeruginosa virulence and biofilm formation after binding on the AmiC sensor, triggering the amiE transcription. Herein, the involvement of the aliphatic amidase AmiE in P. aeruginosa virulence regulation has been investigated. The proteome analysis of an AmiE over-producing strain (AmiE +) revealed an expression change for 138 proteins, including some that are involved in motility, synthesis of quorum sensing compounds and virulence regulation. We observed that the AmiE + strain produced less biofilm compared to the wild type, and over-produced rhamnolipids. In the same line, AmiE is involved in P. aeruginosa motilities (swarming and twitching) and production of the quorum sensing molecules N-acyl homoserine lactones and Pseudomonas Quinolone Signal (PQS). We observed that AmiE overproduction reduced levels of HCN and pyocyanin causing a decreased virulence in different hosts (i.e. Dictyostelium discoideum and Caenorhabditis elegans). This phenotype was further confirmed in a mouse model of acute lung infection, in which AmiE overproduction resulted in an almost fully virulence decrease. Taken together, our data suggest that, in addition to its role in bacterial secondary metabolism, AmiE is involved in P. aeruginosa virulence regulation by modulating pilus synthesis and cell-to-cell communication.